Potenciales relacionados con eventos y comorbilidad en un grupo de adolescentes con trastorno por déficit de atención con hiperactividad. - Zamorano, Ernesto Reyes; Garcell, Josefina Ricardo; Cruz, Lino Palacios; Toca, Elvia Serra; Galindo, Gabriela; Molina, Villa; de la Peña Olvera, Francisco (Salud Mental)
Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder clinically characterized by three core symptoms: deficits in attentional processes, failure in inhibitory control -usually expressed through behavioral and cognitive impulsiveness-, and motor and verbal restlessness. Deficit in attentional resources is the main alteration in patients with this disorder. Attention can be considered as a neurocognitive state of neural preparation that precedes both perception and action. Attention focalizes consciousness in order to filter the constant flux of sensorial information, solve competence between stimuli for parallel processing and recruit and activate cerebral regions necessary to accomplish appropriate responses. Event-related potentials (ERPs) are a technique that has proven useful in the gathering of valuable information in the study of ADHD. One of the most studied ERPs is the P300 component. The most robust finding in the P300 research in ADHD is a decrease in the amplitude of the component in patients when compared to normal controls. This finding is usually interpreted as an evidence for a deficit in attention. ADHD usually presents commorbidity with several disorders; research shows that up to 87% of the children with ADHD present commorbidity with another disorder, up to 60% has either a behavioral or affective disorder commorbid with ADHD. Due to the wide range of disorders that are usually associated with this entity, it is useful in the research of commorbidity to use dimensional diagnostics, that is, a patient with ADHD may have commorbidity with an externalized disorder (EXT) (i.e. oppositionist defiant disorder); an internalized (INT) disorder (i.e. anxiety or affective disorder); or both an externalized and an internalized disorder (MIX). Commorbidity may have important implications in the electrophysiology of ADHD since no homogeneous results have been evident in the scarce research on the subject. Taking into account these considerations, the following experiment was designed in order to answer the question: Patients with the same main diagnostic, ADHD, but different commorbidities (INT and MIX) show different psychophysiological patterns of activation, as measured by ERPs to a continuous performance task? Sixteen patients diagnosed with ADHD by a specialist were recruited. Diagnosis was corroborated by a semi-structured interview, K-SADS-PL-MX, eight of them with an externalized comorbid (EXT) disorder, and eight of them with at least two comorbid disorders, one externalized an one internalized (MIX). A control group (CON) of eight normal subjects with no psychiatric diagnostic and matched by sex was also recruited. All subjects were between 13-16 years old with no history of Central Nervous System damage and normal IQ in the Weschler Intelligence Scale for Children. Brain electrical activity was recorded in the 19 derivations of the 10-20 international system while subjects executed a continuous performance task (CPT). Comparisons of behavioral data between groups showed some significant differences. A one-way ANOVA found differences between groups in the mean reaction time to the first part of the CPT and in the number of false positives in the second part.…